Programma: 14 december Suara Maluku All Stars; 20 december The Wailers; 21 december Let's spend the night together; 22 december Faster Pussycat
Programma: 14 december Suara Maluku All Stars; 20 december The Wailers; 21 december Let's spend the night together; 22 december Faster Pussycat.